PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS OF DEVELOPING TEAM TACTICS IN FOOTBALL (European Journal of Interdisciplinary Research and Development, 2025)
This scientific article is devoted to the topic "Pedagogical and Psychological Foundations for Developing Team Tactics in Football." It highlights the theoretical and practical aspects of forming a team playing style among football players, strengthening mutual cooperation, and developing tactical thinking. The study substantiates that the success of a football team largely depends on the players’ tactical preparedness, level of mutual understanding, and psychological stability. From a pedagogical perspective, the article analyzes methods of gradually forming team actions during the training process, properly distributing roles, and taking into account the individual characteristics of players. From a psychological perspective, it explores ways to cultivate team loyalty, mutual trust, leadership, and emotional stability among players. The article also emphasizes the motivational, communicative, and managerial roles of the coach in developing team tactics. The research results have practical significance for the effective organization of football training sessions, the improvement of team tactics, and the strengthening of athletes’ psychological resilience.